2022
DOI: 10.1007/s10592-022-01447-5
|View full text |Cite
|
Sign up to set email alerts
|

Population genomics study for the conservation management of the endangered shrub Abeliophyllum distichum

Abstract: Natural monuments are IUCN Category III protected areas that play an important role in biodiversity conservation as they provide species refuge and allow species migration. Despite their status, natural monuments are often confined to cultural and fragmented landscapes due to anthropogenic land-use demands. In this population genomic study, we surveyed 11 populations of the endemic shrub Abeliophyllum distichum Nakai (Oleaceae), including five natural monument habitats, covering its range-wide distribution in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 109 publications
3
19
0
Order By: Relevance
“…To assess the level of genetic diversity in this species, we compared our results with those of related studies that used a method similar to that used in this study. Our comparison showed that Z. tyaihyonii has lower genetic diversity ( H e = 0.233) than other species of endemic and woody perennials, such as Abeliophyllum distichum ( H e = 0.319) [ 34 ], Tetraena mongolica ( H e = 0.348) [ 39 ] and Rhododendron rex ( H e = 0.54) [ 35 ]. Given these comparisons, the genetic diversity of Z. tyaihyonii can be considered low.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To assess the level of genetic diversity in this species, we compared our results with those of related studies that used a method similar to that used in this study. Our comparison showed that Z. tyaihyonii has lower genetic diversity ( H e = 0.233) than other species of endemic and woody perennials, such as Abeliophyllum distichum ( H e = 0.319) [ 34 ], Tetraena mongolica ( H e = 0.348) [ 39 ] and Rhododendron rex ( H e = 0.54) [ 35 ]. Given these comparisons, the genetic diversity of Z. tyaihyonii can be considered low.…”
Section: Discussionmentioning
confidence: 99%
“…Protection of trailing-edge populations should be prioritized because the prolonged isolation and successful persistence of such groups suggest their evolutionary potential, which can be useful for the long-term conservation of genetic diversity and phylogenetic history of the species [ 34 , 70 ]. Additionally, isolated populations may accumulate through selective and stochastic processes, the genetic and chromosomal differences that render them independent and distinctive evolutionary entities, and if speciation involves few major changes promulgated by selection and/or genetic drift in small populations, speciation may be relatively rapid, perhaps saltational [ 71 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To apply genomics in population studies (of multiple individuals), methods were developed to reduce the genomic complexity of data, such as "Genotyping by Sequencing -GBS" 29 . GBS methods have been used to genotype thousands of single nucleotide polymorphisms (SNPs) scattered around unknown genomes of many of individuals of different plants 30,31 and animals 32,33 .…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have reported that this shrub has anticancer, antiinflammatory, antiosteoporotic, antiobesity, and antimelanoma effects (Choi et al, 2017;Eom et al, 2020;Lee et al, 2020;Yoo et al, 2020 and, indicating its potential as a crude drug and dietary health supplement. A. distichum was classified as endangered until 2017 owing to reductions in its population and the land area it occupied (Lee et al, 2022); this became a major limiting factor in its application in the food, cosmetic and pharmaceutical industries.…”
Section: Introductionmentioning
confidence: 99%